Examining destination image and Muslim tourists' behavioral intention using the theory of planned behavior - Shazra Ibrahim; Ahmad Albattat; Ali Khatibi (Northern Negros State College of Science and Technology (NONESCOST), 2021)
Destination image has been empirically proven to have a significant influence on the behavioral intention of tourists, while limited studies have been done to explore the relationship between destination image and behavioral intention of a Muslim tourist when visiting a destination. Empirical studies highlight the importance of a positive destination image on the behavioral intention of a Muslim tourist. The primary purpose of this study is to explain the relationship between destination image and behavioral intention with the aid of the theory of planned behavior in the context of Asia and empirical evidence is extracted from various studies conducted in Asian countries. Attracting more Muslim tourists has been a challenge for various countries and while so, the concept of halal tourism has been recently recognized in academia, is in need of research to study the gaps and challenges faced when increasing the number of Muslim tourists in the world. This study highlights the link between destination image and intention to travel of tourists and hence this paper provides a theoretical overview of the Theory of planned behavior and its application to the destination image and behavioral intention of Muslim tourists. Data was gathered from numerous literature compiled by various researchers. Empirical studies conducted in various Asian countries provide evidence that destination image plays a vital role in either creating a positive image or a negative image of the destination and this highly influences the intention of the Muslim tourist to travel to the destination or not. Studies confirm that having Muslim-friendly services attract more Muslim tourists to the destination.